Some issues of improving the statistical accounting of domestic violence in the Republic of Kazakhstan - Biebayeva, A.A.; Dulatbekov, N.O.; Kalguzhinova А.М. (Bulletin of the Karaganda University “Law Series”, 2024)
The article is devoted to the analysis of quantitative and qualitative indicators of domestic violence, highlighted in the official statistics of the Republic of Kazakhstan. Today, our country uses the maximum possible arsenal of means to solve the problem of domestic violence, demonstrates its readiness to identify its causes and neutralize them. The authors used historical and statistical methods of cognition of legal reality, considered the normative provisions of the Kazakh legislation, which forms the legal basis for the prevention of this negative phenomenon. An objective assessment is given of the development of the system of assistance to victims of violence, improvement of information and statistical accounting of domestic violence. Discrepancies were identified and specific comments were made (in particular, on units of measurement, data sources, and the reporting period) when posting statistical information in open sources in accordance with the Methodology for forming a system of basic and additional indicators of gender statistics. To determine the real state of domestic violence, the authors recommend conducting a specific sociological study, and using official data, the results of expert surveys, as well as victims of domestic violence as an empirical database. The article argues for a change in the form of statistical reporting, which includes a list of criminal offenses committed in the family and household sphere, rather than their definition, which is a consolidation of the totality of their signs. The necessity of conducting analytical studies of domestic violence on a regular basis is substantiated.